Latin American Consensus on the management of hypertension in the patient with diabetes and the metabolic syndrome. Issue 6 (June 2019) - López-Jaramillo, Patricio; Barbosa, Eduardo; Molina, Dora I.; Sanchez, Ramiro; Diaz, Margarita; Camacho, Paul A.; Lanas, Fernando; Pasquel, Miguel; Accini, José L.; Ponte-Negretti, Carlos I.; Alcocer, Luis; Cobos, Leonardo; et al.
Abstract : N/A: The prevalence of hypertension, type 2 diabetes mellitus (DM2) and the metabolic syndrome continues to increase in Latin America, while the rates of diagnosis, treatment and control of these disorders remain low. The frequency of the risk factors that constitute the metabolic syndrome and are associated with an increased risk of cardiovascular disease has not diminished since the publication of the previous consensus. This document discusses the socioeconomic, demographic, environmental and cultural characteristics of most associated Latin American countries and partially explains the lack of better results in improving clinical and public health actions that allow high morbidity and mortality rates caused by cardiovascular diseases and DM2 to be reduced through programs aligned with the so-called precision medicine, which should be predictive, preventive, personalized and participatory. The Consensus ratifies the diagnostic criteria expressed in the previous consensus to define hypertension and DM2 but, for the metabolic syndrome, and in the absence of evidence, the recommendation is to implement a cohort study that determines the abdominal perimeter value associated with hard outcomes, such as DM2 and CVD. Meanwhile, we recommend modifying the criterion to more than 94 cm in men and more than 84 cm in women according to WHO recommendations. We also recommend the carrying out of a study that identifies the situation of hypertension and DM2 in people of African ancestry who, in Latin America, exceed 75 million and whose epidemiology does not include solid studies. With respect to the proposed therapeutic targets, we recommended maintaining those defined in the previous consensus, but insisting that early pharmacological management of prediabetes with metformin should be introduced, as should the treatment of diabetic hypertensive patients with a combination therapy of two fixed-dose antihypertensive drugs and management with statins. To increase adherence, the use of different drugs combined in a single pill (polypill) is recommended. The simplification of the therapeutic regimen is accompanied by greater control of cardiovascular risk factors, both in primary and secondary prevention, and has been shown to be cost-effective. The consensus recommends the use of the currently available polypill combining an angiotensin-converting enzyme inhibitor, a statin and aspirin for secondary cardiovascular prevention and in patients with a high cardiovascular risk, such as hypertension patients with DM2.